Electrical and thermal properties of surface passivated carbon nanotube/polyvinylidene fluoride composites. Issue 3 (2018) - Ouyang, Yingxiu; Deng, Yongmao; Li, Dandan; Cai, Zhihong; Xu, Ruijie; Lei, Caihong; Lu, Shengguo
No abstract available